INFLUENCE OF A SOCIALLY-MEDIATED CONTEXTUAL PROFESSIONAL DEVELOPMENT PROGRAM ON PROSPECTIVE SCIENCE TEACHERS’ UNDERSTANDINGS OF NATURE OF SCIENCE, AND INTEGRATING IT INTO THEIR INSTRUCTIONAL PLANNING - Duruk, Ümit (International Online Journal of Education and Teaching, 2020)
This study, which was conducted in 2016-2017 academic year, scrutinized the impact of a purposefully designed professional development program titled ‘NOS-PD’ on the understandings of the Nature of Science (NOS) via instructional practices. Specifically, the purpose of this qualitative multiple-case study was to delineate the impact of a NOS program with a socially-mediated contextual support on the prospective science teachers’ understandings of NOS and integrating it into their instructional planning. In the study process, 13 prospective science teachers took part in an intensive 9-week program conducted at 3 stages (5 weeks + 3 weeks + 1 week) based on a 6-week explicit-reflective NOS instruction plus three weeks of participants’ developing lesson plans with the help of socially-mediated contextual support. Data sources included an open-ended NOS questionnaire and lesson plans. Results indicated that as a result of the NOS instruction, the vast majority of the participants improved their understandings of NOS in an appropriate way. The analysis of the lesson plans revealed three characteristics of participants’ instructional planning for teaching NOS after the NOS-PD program, a) NOS was not sufficiently interpreted except for three NOS components, b) some improvements in terms of the instructional and evaluation strategies were observed, but the knowledge of objectives did not show substantial change, and c) few participants exhibited a robust reported PCK by performing NOS integration at a high level. Keywords: Nature of science translation, professional development program, highly-contextualized nature of science instruction, prospective science teachers